2016
DOI: 10.1086/686729
|View full text |Cite
|
Sign up to set email alerts
|

Choosy Cannibals Preferentially Consume Siblings with Relatively Low Fitness Prospects

Abstract: When an individual can selfishly cannibalize a relative or altruistically set it free, the benefits of altruism will be positively associated with the relative's fitness prospects (the benefits it receives from altruism). We tested the prediction that altruism should be preferentially directed toward high-quality relatives using larvae of the New Mexican spadefoot toad (Spea multiplicata), a species in which tadpoles plastically express omnivore and carnivore ecomorphs. In a no-choice design, we presented carn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…By consuming weak or recently infected individuals, parents could protect their healthier offspring from later infection through eliminating current parasites and a reduction in clutch/litter density (Polis 1981;Hart 1990;Elgar and Crespi 1992;Richardson et al 2010;Lehtonen and Kvarnemo 2015). This possibility ties well to recent work suggesting that the strength of kin selection varies with estimated future fitness (Dugas et al 2016) and suggests that filial cannibalism could be another estimation of risk (including the risk of disease transmission) balanced against offspring potential (Lehtonen and Kvarnemo 2015). While additional explanations for filial cannibalism exist, such as maintaining balance between future costs of offspring rearing and resource levels (Fox 1975;Rohwer 1978;Polis 1981;Manica 2002;Klug and Bonsall 2007), the casting of filial cannibalism as a mechanism that reduces the prevalence of parasites is similar to a smallerscale version of the culling through cannibalism concept outlined above.…”
Section: Devil In the Details: A Cannibal's Perspectivementioning
confidence: 57%
“…By consuming weak or recently infected individuals, parents could protect their healthier offspring from later infection through eliminating current parasites and a reduction in clutch/litter density (Polis 1981;Hart 1990;Elgar and Crespi 1992;Richardson et al 2010;Lehtonen and Kvarnemo 2015). This possibility ties well to recent work suggesting that the strength of kin selection varies with estimated future fitness (Dugas et al 2016) and suggests that filial cannibalism could be another estimation of risk (including the risk of disease transmission) balanced against offspring potential (Lehtonen and Kvarnemo 2015). While additional explanations for filial cannibalism exist, such as maintaining balance between future costs of offspring rearing and resource levels (Fox 1975;Rohwer 1978;Polis 1981;Manica 2002;Klug and Bonsall 2007), the casting of filial cannibalism as a mechanism that reduces the prevalence of parasites is similar to a smallerscale version of the culling through cannibalism concept outlined above.…”
Section: Devil In the Details: A Cannibal's Perspectivementioning
confidence: 57%
“…In animals where aggression can escalate to cannibalism, the majority of studies focus on the causes that underlie the killing and consumption of conspecifics. This previous work has been primarily done in insects (but see Dugas et al 2016b for a similar study done with spadefoot toads) and has yielded a variety of results (interaction between relatedness and size: Dobler and Kölliker 2011 , relatedness effect only: Bilde and Lubin 2001 ; Roberts et al 2003 ), providing no consistent pattern to extrapolate to cannibalistic vertebrates. In D. tinctorius , where there is high offspring investment (i.e., male parental care and low fecundity), we found that large tadpoles (where size is relative between pairs) from sibling dyads were the least aggressive, expressing almost half the amount of aggression compared with large tadpoles from non-sibling dyads ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In systems with sibling aggression, fighting represents an important potential advantage in early development for securing resources ( Drummond et al 2003 ; Naidenko and Antonevich 2009 ); in cannibalistic species, the factors that shape opponent assessment are vital, as there is the threat of interactions escalating to death. Thus, cannibalism is often conditional on the assessment of either the environment (food availability: Mayntz and Toft 2006 ; Dugas et al 2016a , conspecific density: Maret and Collins 1994 , Frankino and Pfennig 2001 ; or a combination of the two: Wildy et al 2001 ) or the opponent (size and relatedness: Dugas et al 2016b , condition: Ibáñez and Keyl 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in growth strategies generally follow predictions of adaptation to ephemeral conditions ( Richter-Boix, Llorente & Montori, 2006 ; Dittrich et al, 2016 ), but we found that this effect was contingent on growing density and food availability. We also found lower cannibalism rates among tadpoles from ephemeral streams, which may be accounted for by the indirect fitness costs involved ( Pfennig, 1997 ; Dugas et al, 2016 ). By comparing two geographically isolated populations using a common garden experiment, we have confirmed that the observed differences at least partly have a genetic basis.…”
Section: Discussionmentioning
confidence: 55%